FECUNDITY AND LENGTH WEIGHT RELATIONSHIP OF BROODSTOCK BROWN TROUT (SALMO TRUTTA M. FARIO) FROM CULTIVATED CONDITIONS IN BANJA LUKA REGION - Klječanin, Jelena; Savic, Nebojsa (Journal of Agricultural Sciences (Belgrade), 2025)
Research on the fecundity and length weight relationship of the broodstock of farmed brown trout (Salmo trutta m. fario) was carried out in the salmonid hatcheries Klašnik and Šiprage, Banja Luka region. The aim of the work was to determine the fecundity of females and the length weight relationship of female and male brown trout from two salmonid hatcheries in the Banja Luka region. 30 females and 30 males per hatchery were analyzed. The age of the females in the Klašnik hatchery was 3+– 4+, and the males were 1+ years old, and in the Šiprage hatchery the females and males were aged 4+– 6+ years. Egg samples from each female were photographed and the number and diameter of eggs in the sample was determined using the "ImageJ" program. A significant correlation (p < 0.01) was found between weight, total length, standard length and body height of females and males from two hatcheries. Total fecundity is significantly lower in females from the Klašnik hatchery (2589±650.85 eggs) than females from the Šiprage hatchery (4618±1541.54 eggs), which had higher body weight. No significant difference (p > 0.05) was found in the relative fecundity, weight and diameter of eggs of females from the hatchery Klašnik (2220±583.71 eggs/kg; 0.097±0.014 g/egg and 5.176±0.232 mm/egg) and Šiprage (2343±801.65 eggs/kg; 0.095±0.02 g/egg and 5.267±0.457 mm/egg). Positive allometric growth (b > 3) was found in females from the Šiprage hatchery, and negative allometric growth (b < 3) in other cases.
Keywords: fecundity, egg weight and diameter, condition factor, brown trout